DELINQUENT BEHAVIOR, ITS CHARACTERISTICS AND DETERMINING FACTORS - Eka Kenchadze (European Scientific Journal, ESJ, 2015)
Delinquent behavior is defined as a criminal action committed by a human confronting the laws of the civil society. Crime understanding is based on the principle of normalization, which means that an individual`s guilt is based on the norms and laws applicable in the civil society. The society conducts control over individual behavior not only by the applicable legislation but also by ethical and moral norms of the society. The crime is a specific form of a behavior that is different from other types of behavior in its contextual load and the community`s assessment of it. Delinquent behavior comprises many components; therefore, according to the complexity of the case, it is the subject of numerous scientific disciplines, including criminology, sociology, psychology, psychiatry, law, etc.